THE IDENTITY OF USTILAGO AMADELPHA VAR. GLABRIUSCULA - MIEN A. RIFAI (REINWARDTIA, 1980)
The host of this smut variety is identified as Panicum repens L. Thefungus is considered conspecific with Ustilago overeemii Cif., which sub-sequently is reclassified as Sporisorium overeemii (Cif.) Rifai, comb. nov.